2020
DOI: 10.3390/ijms21124428
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor Binding Protein 6 Is Secreted in Extracellular Vesicles upon Hyperthermia and Oxidative Stress in Dendritic Cells But Not in Monocytes

Abstract: Recently, insulin-like growth factor binding protein 6 (IGFBP-6) has been shown to play a putative role in the immune system, as monocyte-derived dendritic cells (Mo-DCs) are stimulated by hyperthermia to express IGFBP-6 at both the mRNA and protein levels. However, the presence of IGFBP-6 in extracellular vesicles (EVs) and whether other pro-inflammatory stimuli can induce IGFBP-6 expression in Mo-DCs are not known yet. In this brief report, we show that hyperthermia (39 °C) induces IGFBP-6 secretion associat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…Intriguingly, IGFBP-6 is also an acute-phase protein, as demonstrated by our and other groups in experiments showing that it is rapidly produced in response to damage after DCs and fibroblast exposure to H 2 O 2 [21]. Particularly, H 2 O 2 induces a dose-dependent up-regulation of IGFBP-6 mRNA and protein levels in skin diploid fibroblasts exposed to a sublethal dose of H 2 O 2 [22].…”
Section: Igfbp-6 Has An Important Role In the Immune Responsesupporting
confidence: 57%
“…Intriguingly, IGFBP-6 is also an acute-phase protein, as demonstrated by our and other groups in experiments showing that it is rapidly produced in response to damage after DCs and fibroblast exposure to H 2 O 2 [21]. Particularly, H 2 O 2 induces a dose-dependent up-regulation of IGFBP-6 mRNA and protein levels in skin diploid fibroblasts exposed to a sublethal dose of H 2 O 2 [22].…”
Section: Igfbp-6 Has An Important Role In the Immune Responsesupporting
confidence: 57%
“…Likewise, genetically high levels of N -acetylarginine decrease the levels of IGFBP-6. IGFBP-6 has cancer-protective properties, plays a role in the immune system 60 , 61 and in neuronal protection 62 . N -acetylarginine is a guanidino compound that is capable of inducing seizures in animal experiments; 63 high levels of this compound present in argininemia that is characterized by neurological symptoms 64 .…”
Section: Discussionmentioning
confidence: 99%
“…IGFBP-6 is a critical member of the IGF family and widely exists in human tissues, cells, and body fluids; it can bind to IGF-2 and inhibit the physiological function of promoting cell growth, proliferation, and differentiation mediated by IGF-2 [ 32 ]. IGFBP-6 could promote cell migration and regulate neutrophil activity, which suggests regulating inflammatory immune response and oxidative stress [ 33 , 34 ]. Some studies have indicated that IGFBP-6 could inhibit tumor angiogenesis in multiple systems through the IGF-2-independent pathway [ 35 ].…”
Section: Discussionmentioning
confidence: 99%